Der Juni-Aufstand in der Türkei - Babacan, Errol (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
The article discusses the June Uprising in Turkey in the specific context of neoliberal authoritarianism and Islamic conservatism. It is argued that the occupation of the Gezi-Park and the spontaneous formation of the “Gezi Commune” revealed a communitarian and libertarian political practice in resistance to the accelerated accumulation by dispossession and in opposition to the Kulturkampf tradition fostered by the ruling party.